2018
DOI: 10.1111/ijfs.14020
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bioaccessibility of avenanthramides in cookies made with malted oat flours

Abstract: This study evaluated the effects of malting and in vitro digestion on the bioaccessibility of six avenanthramides (AVNs), soluble phenols (SPs) and antioxidant capacity (ORAC) in cookies (3B, 4B, 5B) prepared with oat flour malted for three (M3), four (M4), five (M5) days, respectively. Control cookies (CTRL) were made with non-malted oat flour (M0). Five-days malting increased the AVN content of native kernels up to 10-folds, whereas SPs and ORAC tripled their values. After the in vitro digestion, AVNs showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…The in vitro digestion (oral, gastric and intestinal phases) was performed on cooked burgers, in triplicate, following the procedure reported in the literature (Ninfali, Mari, Meli, Roselli, & Antonini, 2019) with slight modifications (Table S2). The final suspension derived from the intestinal phase (≈ 35 mL) was used "as-is" for the malondialdehyde (MDA) measurement or centrifuged at 15,000 rpm at +4 °C for 30 min and filtered using 0.45 μm filters for the polyphenol, ORAC, ABTS and DPPH assays.…”
Section: In Vitro Digestionmentioning
confidence: 99%
“…The in vitro digestion (oral, gastric and intestinal phases) was performed on cooked burgers, in triplicate, following the procedure reported in the literature (Ninfali, Mari, Meli, Roselli, & Antonini, 2019) with slight modifications (Table S2). The final suspension derived from the intestinal phase (≈ 35 mL) was used "as-is" for the malondialdehyde (MDA) measurement or centrifuged at 15,000 rpm at +4 °C for 30 min and filtered using 0.45 μm filters for the polyphenol, ORAC, ABTS and DPPH assays.…”
Section: In Vitro Digestionmentioning
confidence: 99%
“…39−41 the basis of the C-type AVAs as a result of the lack of standards. 32,34,35 One scientific report applied 2c as a reference standard for evaluating the A-type AVA concentration equivalently in raw oat samples using high-performance liquid chromatography with diode-array detection (HPLC−DAD) at 340 nm. 33 However, the responses to the ultraviolet (UV) detector of 2c and others AVAs, especially with A-type AVAs being significantly different (Figure S1 of the Supporting Information), would introduce errors when A-type AVAs are quantified on the basis of the standard curve of 2c.…”
Section: C-typementioning
confidence: 99%
“…The sprouted and false-sprouted oats have a higher concentration of AVAs than regular oat; furthermore, it has been noted that there is a higher concentration of A-type AVAs than C-type AVAs in both sprouted and false-sprouted oats, and false-sprouted oat has a better beneficial effect on the prevention of cardiovascular disease than regular oat. The C max of A-type AVA 2p d , observed in a biotransformation study, was found to be 1.7 times higher than C-type AVA 2p in human plasma . However, to date, there are only three A-type AVAs purified from oat (2c d , 2f d , and 4p d ), and two were chemically synthesized (1f d and 2p d ). ,, The bioactivities of A-type AVAs have yet to be reported; furthermore, there is no information regarding the concentrations of A-type AVAs in commercial sprouted oat products.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The cereal grains with higher fibre content displayed lower bioaccessibility levels of polyphenols indicating the ineffectiveness of digestive enzymes in releasing conjugated polyphenols when compared to microbial enzymes ( Table 2 ). Nevertheless, food processing techniques including extrusion, malting, and fermentation treatment can increase the bioaccessibility of phenolic compounds, particularly those with strong bioactive properties such as ferulic acids and AVNs ( Table 2 ) [ 70 , 71 ]. It should be noted that there is a lack of a standardised approach to measuring bioaccessibility and predicting polyphenol bioavailability.…”
Section: Polyphenol Bioaccessibility In the Gi Tractmentioning
confidence: 99%